Nation-wide hypertension screening in Italy: data from May Measurements Month 2017—Europe. (24th April 2019) - Torlasco, Camilla; Faini, Andrea; Makil, Elhassan; Bilo, Grzegorz; Pengo, Martino; Beaney, Thomas; Xia, Xin; Borghi, Claudio; Poulter, Neil R; Tocci, Giuliano; Galletti, Ferruccio; Desideri, Giovambattista; et al.
Abstract: Elevated blood pressure (BP) is a growing burden worldwide, leading to over 10 million deaths each year. May Measurement Month (MMM) is a global initiative organized by the International Society of Hypertension aimed at raising awareness of high BP and to act as a temporary solution to the lack of screening programs worldwide. A similar approach has been used in Italy since 2012, showing inadequate awareness of the consequences of hypertension, a generally increased cardiovascular risk and unsatisfactory BP control in 36% of interviewed individuals. An opportunistic cross-sectional survey of volunteers aged ≥18 was carried out in May 2017, during the joint MMM and World Hypertension Day events. Blood pressure measurement, the definition of hypertension and statistical analysis followed the standard MMM protocol. Screenings were conducted both in cities and villages, indoor and outdoor, by health personnel. Eighty-five sites, involving approximately 300 investigators, took part in MMM17/World Hypertension Day in Italy, screening 10 076 individuals during a month-long period. After multiple imputation, 3099 participants were found (30.8%) to have high BP levels. This was the biggest opportunistic BP screening in a single time-point ever reported in Italy. A significant proportion of individuals had high BP, although it was not possible to differentiate between known treated hypertensive patients with inadequate BP control and as yet undiagnosed hypertensive individuals. Opportunistic screening can reach a significant number of individuals, being a powerful tool for raising awareness and carrying out BP screening.